THE IMPACT OF ADVANCE CARE PLANNING FOR RENAL PATIENTS. Issue 2 (1st June 2013) - Silvester, W; Mawren, D; Detering, K; Wallis, K
Abstract : Background: Research indicates that renal patients are uninformed about care options and have limited knowledge about illness prognosis and trajectories. Accordingly, facilitated Advance Care Planning (ACP) was introduced to the renal unit at the Austin Hospital in 2010. Aim: To evaluate the impact of the introduction of ACP to the Austin Hospital renal unit. Methods: Audit of medical records for (1) 58 patients who received ACP (2010–2012) (2) 58 age and gender matched control patients (2007–2009). Results: The rate of withdrawal from dialysis was significantly higher in the implementation group (IG) (p=0.022), as was the involvement of the patient or family in the decision to withdraw dialysis (p=0.001). Medical decisions to withdraw dialysis was equal between groups (p>0.05) More ACP documents were completed in the IG (MEPOA=67%, SOC=27%, RTC=17%) compared to the control group (MEPOA=5%, SOC=10%, RTC=2%). Significantly more wishes were correctly documented in the IG (p<0.001) and more changes to patient management plans were observed (71%). Patients in the IG were more likely to have their wishes respected (p=0.007) and receive treatment in their best interest (p<0.001). Discussion: The implementation of ACP led to patient wishes being documented and respected, and to dialysis being withdrawn at the patient's or family's request. No difference observed in the involvement of the medical team. More wishes were respected in the IG and more patients received treatment that was in their best interest. Conclusion: Facilitated ACP successfully increased the likelihood of wishes being respected and patients receiving treatment in their best interest.